Bacteriophages and Their Derivatives as Biotherapeutic Agents in Disease Prevention and Treatment. (26th March 2014) - Elbreki, Mohamed; Ross, R. Paul; Hill, Colin; O'Mahony, Jim; McAuliffe, Olivia; Coffey, Aidan
Abstract : The application of bacteriophages for the elimination of pathogenic bacteria has received significantly increased attention world-wide in the past decade. This is borne out by the increasing prevalence of bacteriophage-specific conferences highlighting significant and diverse advances in the exploitation of bacteriophages. While bacteriophage therapy has been associated with the Former Soviet Union historically, since the 1990s, it has been widely and enthusiastically adopted as a research topic in Western countries. This has been justified by the increasing prevalence of antibiotic resistance in many prominent human pathogenic bacteria. Discussion of the therapeutic aspects of bacteriophages in this review will include the uses of whole phages as antibacterials and will also describe studies on the applications of purified phage-derived peptidoglycan hydrolases, which do not have the constraint of limited bacterial host-range often observed with whole phages.